2014
DOI: 10.1089/end.2014.0408
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Perirenal Instillation of Bupivacaine After Tubeless Percutaneous Nephrolithotomy Under Spinal Anesthesia: A Double-Blind, Placebo-Controlled Clinical Trial

Abstract: Intermittent perirenal instillation of bupivacaine via the nephrostomy tract after PCNL decreases the need for more systemic narcotics and provides acceptable analgesia in the postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Scientific findings support using paravertebral block or epidural anesthesia before PCNL to minimize the postoperative pain [ 16 , 17 ]. Local injection of analgesic drugs is also effective for this treatment [ 18 , 19 , 20 , 21 ]. Preventive preoperative intravenous or subarachnoid spinal analgesia was also described [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scientific findings support using paravertebral block or epidural anesthesia before PCNL to minimize the postoperative pain [ 16 , 17 ]. Local injection of analgesic drugs is also effective for this treatment [ 18 , 19 , 20 , 21 ]. Preventive preoperative intravenous or subarachnoid spinal analgesia was also described [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sharifi et al . [20] evaluated the efficacy of intermittent perirenal instillation of bupivacaine posttubeless PCNL under spinal anesthesia and observed that the pain score (VAS) at various time intervals and concluded that bupivacaine provided a more acceptable analgesia; however, it was statistically insignificant. Shah et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although perhaps not sufficient by itself, LA seems to improve pain control when associated with regional anesthesia as Sharifi and colleagues reported in a randomized trial of nephrostomy tract instillation with bupivacaine after PCNL under spinal anesthesia; LA was found to decrease the need for more systemic narcotics and provide acceptable analgesia in the postoperative period. 3 …”
Section: Discussion and Literature Reviewmentioning
confidence: 99%